PENDEKATAN KREATIF PENDIDIKAN JASMANI DAN OLAHRAGA UNTUK PENINGKATAN KESEHATAN DAN GAYA HIDUP SEHAT - Parlindungan, Doby Putro (Universitas Muhammadiyah Jakarta, 2017)
Physical education and sport have always as subjects that could improve health and create a healthy lifestyle of students in school and outside of school. This is a great opportunity for physical education teachers and sports actively create on creating effective learning in order to achieve these objectives. Creative approaches undertaken by physical education teacher and sports has three themes, namely creative teaching, taught to be creative, and creative learning. The third theme is applied and adapted to the principles of physical education and sport, namely safety, impact drills, health benefits, and increased activity.